A Study On The Determinants Of Marketing Effectiveness Of Mobile Marketing Communication On Social Media For Small And Medium Enterprises & Neighborhood Stores’ In USA - Shamsudeen, Shajahan; Khalufi, Nasser (Archives of Business Research, 2018)
Purpose of the research was to ascertain the determinant of marketing effectiveness of SMEs and Neighborhood stores’ mobile marketing communication on social media and to explore its contribution to customers' online and instore shopping experience. The study also portrayed customers’ perception towards the mobile marketing message and its credibility as well. During data analysis, it was established that SMEs and Neighborhood stores which were using social media for Mobile marketing communications regularly as a part of their promotion strategy. The study findings predicted the marketing effectiveness of mobile marketing communication by resorting to Multiple Regression analysis. The study findings suggested that by focusing on mobile marketing content, message credibility, authenticity, its relevancy to weekly shopping along with human supports through chats and customer service ( empathy) and consistent quality and performance ( Reliability) can give an edge to the SMEs and Neighborhood stores over national and global brands in their neighborhoods. Majority of the respondents commented that the mobile phone were the sole mate and companion in 24X7 mode in their life journey. The survey participants welcomed mobile marketing by the SMEs and Neighborhood stores through MMS, Push messages , Ringless voicemail, Location based services and Mobile Apps with credible message. Therefore, It is suggested that SMEs and Neighborhood stores should take advantage of study findings by predicting the marketing effectiveness of mobile marketing communication which influence the Marketing ROI of the firm and purchase intent of present and prospective customers while planning their weekly shopping online or instore.